What are The Benefits of Five-Toed Socks? A Scoping Review - Roberto Tedeschi (Lithuanian Sports University, 2023)
Background. The use of five-toed socks can be a valid prevention option against interdigital problems and a valuable sensory stimulus in walking. However, nowadays, they are hardly ever suggested because they are often little known or disregarded by clinicians dealing with podiatric problems. The aim. This scoping review aims to map and summarise the literature to identify interventions using five-toed socks Methods. Four databases were searched up to December 2022. Studies that considered the use of five-toed socks could be included. All interventions and contexts were considered. No restrictions were applied regarding language, study design and publication type. Grey literature and reference lists of included articles were not identified. The results were presented in numerical and thematic form. Results. Out of 23 initially identified studies, only 4 met the inclusion criteria for this scoping review. The majority of the included articles were randomized controlled trials (RCTs) and involved participants of different ages, including both sporty and non-sporty individuals, who used five-toed socks as part of the intervention. It is worth noting that the authors focused solely on conservative interventions, with all 4 studies investigating the effects of wearing five-toed socks for more than one week. Conclusions. This is the first scoping review to provide a comprehensive overview of the topic. The results revealed clear gaps in primary research, confirming that current management is based on knowledge of five-toed socks. This review may be useful for general management and may provide a starting point for future research. Keywords: foot care, foot problems, five-toed socks, toes.